The Role of Programmed Death Ligand 2 (PD-L2) in Regulation of Immunopathology in Schistosoma mansoni Infection. - Miller, Emily. (Tufts University. Tisch Library., 2018)
Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.